Neurobiology of anti-social personality disorder (Archives of Clinical Psychiatry, 2005)
Violence and crime have been increasing considerably in urban societies. As a consequence, some efforts have been made aiming at a better understanding of antisocial bevaviour. Apart from psychosocial factors, some evidences suggest the occurrence of biological factors in the pathogenesis of antisocial personality disorders (ASPD). Neuroimaging studies have shown the involvement of prefrontal areas, especially orbitofrontal cortex, and amygdala. Also, impaired serotonin (5-HT) neurotransmission has been implicated, since patients with ASPD present alterations in measures of 5-Ht system, such as blunted hormonal response to 5-HT pharmacological challenges and reduced 5-HT receptors numbers. A comprehensive approach of antisocial behavior, including biological and psychosocial aspects could lead to the development of new techniques for prevention and intervention in ASPD.